2018
DOI: 10.1002/sctm.17-0246
|View full text |Cite
|
Sign up to set email alerts
|

Influencing the Fate of Cardiac and Neural Stem Cell Differentiation Using Small Molecule Inhibitors of ALK5

Abstract: In this study, 50 tri‐substituted imidazoles (TIs), which are analogs of the small molecules TA‐01 and SB203580, were synthesized and screened for cardiomyogenic activities. Several TIs displayed cardiomyogenic activities when applied during the differentiation from days 3–5. The TIs did not affect the Wnt/β‐catenin pathway during cardiomyogenesis and the likely mechanism of action is through the inhibition of ALK5 of the TGFβ pathway. Interestingly, these TIs promoted the neural differentiation of human pluri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…Small molecule inducers play an important role in stem cell differentiation. Many tri-substituted imidazole molecules have been reported to promote the neural differentiation of human pluripotent stem cells 9 days post treatment [ 21 ]. We also verified whether imidazole group and SDF-1α in GelMA-imid/SDF-1α hydrogel could promote hAMSC differentiation, and the results were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Small molecule inducers play an important role in stem cell differentiation. Many tri-substituted imidazole molecules have been reported to promote the neural differentiation of human pluripotent stem cells 9 days post treatment [ 21 ]. We also verified whether imidazole group and SDF-1α in GelMA-imid/SDF-1α hydrogel could promote hAMSC differentiation, and the results were shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it is also very important to promote the differentiation of stem cells. Imidazole molecules are proved to promote the differentiation of pluripotent stem cells into neural cells [ 21 ]. It is also found that hydrogel containing imidazole groups can repair spinal cord injury by promoting ECM remodeling [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transforming growth factor-beta (TGF-β) signaling pathway is particularly crucial for embryonic development as it regulates pathophysiological processes of various organs [21]. Inhibition of the TGF-β signaling pathway accelerates the differentiation of neural-or endothelial-lineage cells, although the exact role of TGF-β signaling might vary depending on cell type and environment [22][23][24]. Therefore, we hypothesized that the regulation of the TGF-β signaling pathway could play key roles in enhancing the efficiency of hPSC differentiation into BME-like cells and acquiring the BBB phenotype by inducing co-differentiation into neural cells and ECs.…”
Section: Introductionmentioning
confidence: 99%
“…Due to high-cost considerations and the need for high-throughput mechanism insights into drug screening applications with human cells, such a system for protein quantification is particularly valuable for studies with human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). Indeed, the Wes has been already applied in several cases recently, including signaling pathway inquiries with hiPSC-CMs (35), cardiac pharmacology and toxicology (36), hiPSC differentiation (37,38), gene therapy (39) and quantifying ion channel expression to assess maturity (34).…”
Section: Introductionmentioning
confidence: 99%